Comprehensive Analysis of Gallstone Composition and Association with Risk Factors in Bangladesh: Insights into the burden and outlook for prevention and management. - Farhad Ul Hassan, ASM; Hossain, ABMB; Akther , SMQ; Ahmed; Islam , MJ; Suma , SA; Khan, MS (Journal of Shaheed Suhrawardy Medical College, 2024)
Gallstone is as ancient as human civilization. It has been found in the gallbladders of Egyptian mummies, dating back to 1000 BC. Gallstone is one of the diseases prevalent in developed nations but it is less prevalent in the developing populations that still consume traditional diets. Gallstones are formed in the gallbladder, from the constituents of bile cholesterol and calcium bilirubinate are the main chemical compounds present in gallstones and their precipitation in bile is induced by multiple aetiological factors. The prevalence and the chemical composition of gallstones vary from population to population. This indicates the involvement of multiple risk factors in the pathogenesis of gallstones. Therefore investigation of the chemical composition of gallstones is primarily important to recognize the correlation with the risk factors for gallstones disease in a community. J Shaheed Suhrawardy Med Coll 2022; 14(2): 3-10